Call admission control in an ATM network by using the burst-length distribution - Sridhar, Sripathi; Erke, Tapio J.; Sharma, A.B.; Takahashi, Kenzo; Kolkki, Raimo; The Government of Netherlands (Bangkok : Asian Institute of Technology, 1992)
The future Broadband Integrated Services Digital Network (B I SDN) based on Asynchronous Tra n sfer Mode (ATM) concept will require the efficient handling of a v e ry diverse mix of traffic. Several important issues related to the quality of service requirements by the user's need to be answered. Efficient use of the available resources requires procedures for congestion control. Connection Admission Control (CAC) is an important part of the congestion control mechanisms in B-ISDN . CAC schemes suggested so far have considered only the peak cell rate and the average cell rate as the traffic parameters. Average burst l ength although found to be a critical parameter has not been included as a parameter for traffic estimation. The Three Parameter Scheme suggested by Chamila [CHAMILA(1992)] uses the burst length as a third parameter . However the use o f burst l ength involves the burst length distribution which plays an i mporcanc r ole i n the cell loss probability . This has been neglected by Chamila. This research work f ocuses on t he inclusion o f burst length distribution as a parameter for traffic estimation. It has been demonstrated that the burst length distribution can be used to determine the worst case traf fie situation. A new Connection Admission Strategy has been proposed which uses the burst length distribution as a parameter along with the peak cell rate, average cell rate and average burst length. It is demonstrated that the proposed scheme provides a tighter bound on the cell loss probability when compared to the Three Parameter Scheme . The results of the study suggests that the burst length distribution is a critical parameter effecting the cell loss probability and its inclusion as a source traffic descriptor allows us to obtain a higher multiplexing gain .
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1992
Keywords: Telecommunication -- Traffic